THE RELATIONSHIP OF BODY COMPOSITION AND THE INTENSITY OF PHYSICAL ACTIVITY OF PREPUSCENT CHILDREN (Fiep Bulletin - online, 2015)
Identify the relationship of school period with the body composition and the intensity of physical activity of prepubescent male and female children. Methods: For the study, were randomly selected 55 boys and 48 girls, age 7 to 8 years old. Anthropometrics measurements: BMI and sum of 7 skin folds. For the intensity of physical activity the children were divided in three groups according to Bouchard (1983). The physical inactivity corresponding to the values of 1 and 2 (1 to 1,5 METs); light activity 3  4 - 5 (1,6 to 3,4 METs), moderate/high activities 6 to 9 (above 3,5 METs). For data analyses, ANOVA´s two-way and Pearson moment correlations were used, with p
Keywords: Children; physical activity and body composition.